EFFECT OF HEATING AT 400OC AND 430OC FOR 5 AND 15 MINUTES ON FRICTION STIR WELDING JOINTS OF Al-Si ADC12 AND AC4C ALLOYS - Muchlis, Abdul (Universitas Gunadarma, 2016)
Friction stirwelding is a joint technique for material in solid phase condition. Friction stir welding has usually done for aluminium because it is the easiest of joint technique for metals. Materials used in this research are hypoeutectic Al-Si ADC12 and AC4C alloys and welding tool is High Speed Steel (HSS). ADC12 has 11.86% Si and AC4C have 7.11% Si. Friction stir welding was done for 1 pass with rotation welding tool of 1200 rpm and speed of motion of 5-7 mm/minutes. Macrostructure and microstructure of both alloys were observed in this study following by hardness testing. The welding joints of both Al-Si alloy consisted of stir zone, thermomechanical affected zone either in retreat and advance sides and base metal. The stir zone of Al-Si ADC12 has Al-α and fine particle Si, is smaller than Al-Si AC4C. ADC12 and AC4C after friction stir welding were heating at 4000C and 4300C for 5 and 15 minutes. A lot of porosities were found at ADC12 joint whereas on AC4C a few porosity. Microstructure of this aluminium alloy after heating with 400oC become bigger. Whereas 430oC shown particle Si more large and rough. It few interval time of heating so particle silicon is larger. The heating with 430oC at ADC12 was occured fail of material, whereas at AC4C is fine. Hardness of material Al-Si at base metal, stir zone,heat affected zone and termomechanically affected zone. Heating made the stir zone of Al-Si ADC12 became harder at 400oC for 15 minutes.Heating made the stir zone of Al-Si AC4C became harder at 400oC for 15 minutes. Keywords : ADC12, AC4C, Welding, crystallization, heating